The growth-employment-poverty nexus in Latin America in the 2000s: Mexico country study - Guillermo Cruces; Gary Fields; David Jaume; Mariana Viollaz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
During the 2000s Mexico grew less than the average for Latin America. Labour market indicators exhibited mixed changes, with improvements over the period for some of them and deterioration for others. The country was severely hurt by the international crisis of 2008, but Mexico surpassed its pre-crisis output levels by 2012. Most labour market indicators were affected negatively by the crisis, and labour earnings and poverty indicators had not recovered their pre-crisis levels by 2012.
Keywords: O15; J01; J30; 330; Mexico; Latin America; inclusive growth; labour market; poverty